A framework for analyzing trade-offs in cost and emissions in power sector. (15th March 2020) - Kumar, Pankaj; Banerjee, Rangan; Mishra, Trupti
Abstract: Current electricity markets operate on a cost minimizing objective for power supply. However, countries across the world need to decarbonize their power systems in line with their policy objectives to mitigate climate change. In this context, this paper presents a framework to analyze synergies and trade-offs in cost and emission minimization strategies in the power sector. Emission minimizing objective can reduce emissions from existing fleets having flexibility in electricity supply, regardless of renewable energy capacity additions. This framework can also provide us with win-win strategies for reducing emissions while keeping costs low. An optimization model is developed for case study of India with data of 568 coal and 199 gas thermal units to analyze alternative real time dispatch and operating strategies. The cost and emission optimal supply strategies are compared in terms of power plant operations, emission reductions, and resulting cost of carbon abatement. The results show that 9.8% of carbon dioxide emissions can be reduced with 19% increment in the cost of electricity in emission minimizing strategy with respect to cost minimization. The operations in emission optimal supply strategy require additional 28 million dollars per day. The cost of carbon abatement is 99–129 dollars per tonne. Highlights: Cost and emission minimizing strategies are presented for power sector operations. The method provides operating strategy to reduce emissions with existing inventory. Emissions can be reduced by 9.8% with respect to baseline. The framework is useful for all countries to assess trade-offs in operating strategies.